Daily Hemodialysis Helps Critical Nephritic Lupus Patient: A Case Report - Fitri, Lillah; Aditianingsih, Dita (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Nephritic lupus is the most common and serious complication of systemic lupus erythematosus (SLE) and is associated with a worse prognosis. Hemodialysis is effective in alleviating symptoms and renal involvement in a nephritic lupus patient. Method: A 33-year-old female was diagnosed with SLE in September 2017. She was also diagnosed with diffuse membranous proliferative glomerulonephritis, as confirmed with a kidney biopsy. She complained of gradual onset limb weakness and peripheral edema 3 months before admission. She was treated with 6 cycles of cyclophosphamide and continued with methylprednisolone 16 mg once daily, hydroxychloroquine 200 mg once daily, and myfortic 360 mg twice daily. A day before ICU admission, her creatinine level was increased to 4.6 mg/dl with an estimated GFR of 12 ml/min and her symptoms then worsened into seizures and lung edema. Daily hemodialysis with heparin-free SLEDD was performed. About 2L was extracted for the first 6 hours with Qb 150 ml and Qd 300 ml and was continued until the day after. For the next 4 days, 3L was extracted per day with Qb 200ml and Qd 500 ml. The patients’ hemodynamic status was within normal limits during dialysis period. The condition improved and the patient was transferred to the ward. Discussions: Hemodialysis is a way to solve kidney problems in in nephritic lupus and SLE patients in general. It should not only be employed for mainly kidney problems but could be beneficial in autoimmune patients with conditions such as nephritic lupus. Slowly extracted dialysis type would be a good and inexpensive option to resolve nephritic lupus in compromising lupus patients. Filtration is ensured and solute removal is achieved relatively equivalent to CRRT. Conclusion: Daily hemodialysis could increase renal salvation by providing less creatinine serum and removing accumulated fluids. The SLEDD type could be used for critical nephritic lupus patients with reduced hemodynamic perturbations, minimal anticoagulant, and lower cost.